DNA INSTABILITY ASSOCIATED WITH FOLATE DEﬁCIENCY - Salih, Alyaa Abdulhadi (PT. Antis International Publisher, 2024)
Folate, also referred to as Vitamin B9, is a type of vitamin that dissolves in water and plays a central role in preserving the integrity of DNA molecules and gene expression through the construction of DNA and methylation. Folate cannot be synthesised in vivo and must be obtained from the diet, particularly fruits and green leafy vegetables. deficiency of folate increases the risk of DNA stability due to uracil misincorporation into the DNA backbone and chromosome breaks, it can lead to the accumulation of deoxyuridine monophosphate (dUMP) which impairs the pathway of dTMP synthesis. in addition, it reduces the availability of methyl donors which causes impaired methylation patterns. Finally, it can generate oxidative stress leading to mtDNA damage and eventually to genomic instability. Different studies and measurement methods have produced varying evidence on the connection between folate and DNA stability, So we encourage to increase in folic acid intake for at-risk groups, but more rigorous human studies are needed before scientifically based public health recommendations about dietary requirements can be made.